Relevance of CEA and LDH in relation to KRAS status in patients with unresectable colorectal liver metastases. Issue 4 (23rd December 2016) - Connell, Louise C.; Boucher, Taryn M.; Chou, Joanne F.; Capanu, Marinela; Maldonado, Stephanie; Kemeny, Nancy E.
Abstract : BACKGROUND: While the significance of carcinoembryonic antigen (CEA), lactate dehydrogenase (LDH), and Kirsten rat sarcoma (KRAS) status as individual prognostic factors for patients with metastatic colorectal cancer has been addressed, the relationship and interdependence between these prognostic factors on survival is limited. METHODS: Patients with unresectable colorectal liver metastases with known KRAS status, and with baseline CEA and LDH levels who were treated with hepatic arterial infusion and systemic chemotherapy were identified. Patients were divided into two groups: hepatic‐only disease and extra‐hepatic disease. RESULTS: A total of 193 patients were included: 121 with hepatic‐only and 72 with extra‐hepatic disease. In the hepatic‐only group, median overall survival (OS) was 55 months. On multivariate analysis, KRAS mutated tumors (HR 1.7, P < 0.05), LDH >200 U/L (HR 2.0, P < 0.05), and prior chemotherapy (HR 2.1, P < 0.05) had lower OS. In patients with extra‐hepatic disease, median OS was 32 months. On multivariate analysis, baseline CEA >200 ng/mL (HR 2.1, P = 0.051), LDH >200 U/L (HR 3.8, P < 0.05), and right‐sided tumors (HR 2.8, P < 0.05) had lower OS. CONCLUSIONS: This analysis verifies two distinct patterns in terms of biomarkers in patients with unresectable colorectal liver metastases. In patients with hepatic‐only disease, KRAS mutation and elevated LDH negatively influenced survival. In patients with extra‐hepatic disease, elevated LDH negatively impacted survival.